Anti-IgLON5 Disease: A New Bulbar-Onset Motor Neuron Mimic Syndrome. Issue 2 (2nd March 2021) - Werner, Jana; Jelcic, Ilijas; Schwarz, Esther Irene; Probst-Müller, Elisabeth; Nilsson, Jakob; Schwizer, Bernhard; Bloch, Konrad Ernst; Lutterotti, Andreas; Jung, Hans-Heinrich; Schreiner, Bettina
Abstract : Objective: To expand the spectrum of anti-IgLON5 disease by adding 5 novel anti-IgLON5–seropositive cases with bulbar motor neuron disease-like phenotype. Methods: We characterized the clinical course, brain MRI and laboratory findings, and therapy response in these 5 patients. Results: Patients were severely affected by bulbar impairment and its respiratory consequences. Sleep-related breathing disorders and parasomnias were common. All patients showed clinical or electrophysiologic signs of motor neuron disease without fulfilling the diagnostic criteria for amyotrophic lateral sclerosis. One patient regained autonomy in swallowing and eating, possibly related to immunotherapy. Conclusion: IgLON5 disease is an important differential diagnosis to evaluate in patients with bulbar motor neuron disease-like phenotype and sleep disorders. There is need for a deeper understanding of the underlying pathobiology to determine whether IgLON5 disease is an immunotherapy-responsive condition.